Pregnancy screening prior to chemotherapy administration. Issue 10 (October 2016) - Hu, L.; Kichenadasse, G.; Martin, H.; Roy, A.; Sukumaran, S.; Vatandoust, S.; Koczwara, B.; Karapetis, C. S.
Abstract : A retrospective case notes review was performed to determine compliance with screening for undetected pregnancy prior to commencement of chemotherapy at Flinders Medical Centre. All female patients aged 18–55 who commenced chemotherapy between January and December 2014 were included. During the first 12 months, for women identified as having childbearing potential, pre‐chemotherapy pregnancy screening was performed only in 40% of patients under 40 years and in 20.5% of the entire age range.